2008
DOI: 10.1212/01.wnl.0000304051.01650.23
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes and gene expression implicate the MAPT region for Parkinson disease

Abstract: Background-Microtubule-associated protein tau (MAPT) has been associated with several neurodegenerative disorders including forms of parkinsonism and Parkinson disease (PD). We evaluated the association of the MAPT region with PD in a large cohort of familial PD cases recruited by the GenePD Study. In addition, postmortem brain samples from patients with PD and neurologically normal controls were used to evaluate whether the expression of the 3-repeat and 4-repeat isoforms of MAPT, and neighboring genes Saitoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 40 publications
2
75
0
Order By: Relevance
“…9,18 To determine which of the associated alleles in the MAPT locus were present in H1 (previously associated with PD [19][20][21][22][23][24] ) a two-locus haplotype association analysis of rs1981997 and SNPs in the MAPT region was carried out using PLINK. 15 Although we are aware that the sample size of this cohort has a limited power and a GWAS would probably fail to find any associated locus after correcting for 514 799 independent tests, we decided to carry out this analysis to look for specific PD risk loci in the Dutch population.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…9,18 To determine which of the associated alleles in the MAPT locus were present in H1 (previously associated with PD [19][20][21][22][23][24] ) a two-locus haplotype association analysis of rs1981997 and SNPs in the MAPT region was carried out using PLINK. 15 Although we are aware that the sample size of this cohort has a limited power and a GWAS would probably fail to find any associated locus after correcting for 514 799 independent tests, we decided to carry out this analysis to look for specific PD risk loci in the Dutch population.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…60,61 Two SNPs were present within the tau 5' leader. 61,62 The first SNP located at nucleotide 108 is a C to T transition and the second SNP is a deletion of a cytosine at position 199. The two SNPs were tested individually in an A-capped monocistronic RNA to determine if there was an effect on IRES activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro aggregation assays have shown that co-incubation of tau and α-synuclein promotes the aggregation of both protein species (Giasson et al, 2003). A recent association study confirmed the genetic link between MAPT and PD and showed a significantly higher expression of 4R tau in PD brains compared to controls (Tobin et al, 2008). While the mechanism by which tau influences PD pathogenesis remains unclear, tau protein has emerged as the central player in many neurodegenerative diseases.…”
Section: Tau As a Genetic Risk Factor For Neurodegenerative Diseasesmentioning
confidence: 99%